Highly photocatalytic active r-GO/Fe3O4 nanocomposites development for enhanced photocatalysis application: A facile low-cost preparation and characterization. Issue 22 (15th November 2021) - Imran, Mohd; Alam, Md. Mottahir; Hussain, Shahir; Ali, Mohammad Ashraf; Shkir, Mohd; Mohammad, Akbar; Ahamad, Tansir; Kaushik, Ajeet; Irshad, Kashif
Abstract: This research explores reduced graphene oxide-Fe3 O4 nanocomposites synthesis, characterization, and it's ability to degrade methylene blue dye using sodium lamp as the visible white light source. The modified co-precipitation method was employed for the synthesis of the photocatalyst. The photocatalyst was further characterized by various characterization techniques. Moreover, photocatalytic activity was performed by varying performance conditions, and analyzed the results. It was found that photocatalyst has highly active performance at the working conditions of pH 12 with 50 mg catalyst for 10 ppm methylene blue dye solutions and produced 98.3% degradation of the dye within 80 min. It was also observed that minor positive performance was observed on varying temperature and catalyst concentration. The photocatalytic activity was found highly dependent on the pH of the solution and increased with an increase in pH. Additional studies were also performed by adding some amount of hydrogen peroxide in the solution without changing its pH. It was also noted that as the amount of hydrogen peroxide was increased in the solution, there was an increment in the degradation of the dye. A maximum of 98.8% degradation was recorded with the 9 ml addition of hydrogen peroxide-containing 25 mg catalyst, pH 8, and at 40 °C reaction temperature within 70 min of irradiation.